Recent advances in the solar thermochemical splitting of carbon dioxide into synthetic fuels - Rony, Zahidul Islam; Mofijur, M.; Ahmed, Shams Forruque; Kabir, Zobaidul; Chowdhury, Ashfaque Ahmed; Almomani, Fares (Frontiers in Energy Research, 2022)
One of the most significant difficulties facing humanity in the twenty-first century is meeting the world's ever-increasing energy needs. Fossil fuels provide about 80% of the world's energy needs, which in turn contributes to global warming and has other negative consequences for the environment. One of the major causes of global warming is the excessive accumulation of carbon dioxide (CO2) into the atmosphere. CO2 emissions into the atmosphere have increased dramatically in recent years, and this is one of the primary drivers of global warming. In response to the limits of traditional techniques, several unique technologies have been developed. The purpose of this review is to summarise the most recent updates on metal oxide-based thermochemical cycle technologies that are used in CO2 conversion, as well as detailed information about their working principle and types of thermochemical cycle technologies currently in use, as well as operating conditions. The information on recent advances in metal oxide-based carbon dioxide conversion into fuels will be beneficial to both the industrial and academic sectors of the economy.